Ischemic Stroke: Do Not Forget Lyme Neuroborreliosis - Gabriela Moreno Legast; Armin Schnider; Nicolas Nicastro (Case Reports in Neurological Medicine)
Lyme neuroborreliosis is a rare cause of ischemic stroke; it has only been described in case reports and mostly in Europe. Diagnostic criteria have been proposed for Lyme neuroborreliosis but the association with a cerebral ischemic presentation is not always straightforward. We here describe the case of an 83-year-old man for whom we strongly suspect Lyme neuroborreliosis as the etiology of his stroke. This case reminds us of the importance of a thorough history taking (i.e., tick bite) and to perform the adequate ancillary tests accordingly (lumbar puncture) so as to propose validated treatment.